Design, construction, and evaluation of transformer-based orbital shaker for coffee micropropagation - Edwin Romeroso Arboleda (National Research and Innovation Agency, 2022)
This study offers a novel solution to deal with the complicated electronic circuitry for speed controller and too complex mechanical design of rotating mechanism of an orbital shaker. The developed prototype used a transformer that varies the supply voltage to control the speed of rotation of the orbital shaker. The prototype has five speed levels which depend on the input voltage. These speeds are 180 rpm at 12 V, 258 rpm at 15 V, 360 rpm at 18 V, 427 rpm at 21 V, and 470 rpm at 24 V. The prototype was tested to run continuously for 48 hours for each speed level, with speed being measured every hour using a tachometer. Statistical computation shows that the speed remains constant for the entire 48 hour period. Evaluation of results shows that the speed controller and the novel mechanical design for the orbital shaking motion achieved their functions. For this reason, it can be concluded that the prototype is durable and safe for use in orbital shaking applications.